Studi Kasus: Identifiksi Patogen Penyebab Penyakit pada Burung Merpati (Columba livia domestica) di Pasar Hewan Kota Surabaya - Putri, Mariana Febrilianti Resilinda; Kendek, Irfan Alias; Mandala, Aletha Yuliana; Malelak, Marlin Cindy Claudia; Yanardhini, Ganis; Moekti, Bima Satria (Jurnal Veteriner Nusantara, 2025)
Pigeons (Columba livia) are a species that often adapt well to urban environments and play an important role in the ecosystem as vectors for the spread of various parasites and zoonotic pathogens. This study aimed to identify the presence of gastrointestinal parasites, blood protozoa, and ectoparasites in pigeons originating from live animal markets in Surabaya, Indonesia. Samples were taken from six pigeons showing clinical symptoms such as diarrhea, anorexia, and weakness. Microscopic examination of feces revealed the presence of Capillaria sp. and Raillietina sp. worm eggs, as well as Eimeria sp. and Haemoproteus columbae protozoan parasites found through blood smears. In addition, ectoparasite identification included Columbicola columbae, Menopon sp., and Menacanthus stramineus. These results show that pigeons in live animal markets have the potential to be a source of parasite and zoonotic disease transmission and have a negative impact on poultry and human health. Therefore, it is important to control parasites through improved sanitation, better habitat management, and vector control to reduce the risk of disease transmission.